Searching for prehistoric campfires in the Patagonian Andes, Southern Chile, with implications for the global-scale debate on the use of forest resources in pre-industrial societies - Raven Garvey; Thomas Urban (Quaternary Environments and Humans)
Little is known about human occupation of the Aysén region of Patagonia beyond a relatively small number of cave and rock shelter sites. Recent magnetic survey and auguring over a broad area in the vicinity of known sites yielded no cultural material, drawing attention to ongoing debate about human use of forests in prehistory.